(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The author takes an attempt to look on technological and information revolution in context of creating a new professional value on the labour market. As shown the differ-ence between generations has an influence on the performance of the actual work be-cause of personal aspirations and needs. The main goal of this article is to outline a new dehumanized quality of workand systematized new occupations concentrated around the creation of an educational platform. It may constitute added value to the polishlabour market.